Mucosa: Key Interactions Determining Sexual Transmission of the HIV Infection - Gonzalez, Sandra M.; Aguilar-Jimenez, Wbeimar; Su, Ruey-Chyi; Rugeles, Maria T. (Frontiers in Immunology, 2019)
In the context of HIV sexual transmission at the genital mucosa, initial interactions between the virus and the mucosal immunity determine the outcome of the exposure. Hence, these interactions have been deeply explored in attempts to undercover potential targets for developing preventative strategies. The knowledge gained has led to propose a hypothetical model for mucosal HIV transmission. Subsequent research studies on this topic further revealed new mechanisms and identified new host-HIV interactions. This review aims at integrating these findings to inform better and update the current model of HIV transmission. At the earliest stage of virus exposure, the epithelial integrity and the presence of antiviral factors are critical in preventing viral entry to the submucosa. However, the virus has been shown to enter to the submucosa in the presence of physical abrasion or via epithelial transmigration using paracellular passage or transcytosis mechanisms. The efficiency of these processes is greater with cell-associated viral inoculums and can be influenced by the presence of viral and immune factors, and by the structure of the exposed epithelium. Once the virus reaches the submucosa, dendritic cells and fibroblasts, as recently described, have been shown in vitro of being capable of facilitating the transfer of viral particles to susceptible cells, leading to viral dissemination, most likely in a trans-infection manner. The presence of activated CD4+ T cells in submucosa increases the probability of infection, where the predominant microbiota could be implicated through the modulation of an inflammatory microenvironment. Other factors such as genital fluids and hormones could also play an essential role in HIV transmission. Here, we review the most recent evidence described for mucosal HIV-transmission contributing with the understanding of this phenomenon.